2022
DOI: 10.17061/phrp3222214
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the space and conditions for co-leadership in co-design: an evaluation of co-facilitator training for culturally and linguistically diverse consumers

Abstract: Enabling the space and conditions for co-leadership in codesign: an evaluation of co-facilitator training for culturally and linguistically diverse consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Process evaluation of codesign indicates that reflexive practice, coleadership models and reciprocal learning are valued strategies to support the inclusion of theory into a user-driven approach to healthcare codesign. 30 Strategies that require discussion, action and reflection beyond codesign meetings necessitate additional time and resource, which must be recognised and supported by leaders and researchers as an important part of preparing for and undertaking this study. 6,20 AUTHOR CONTRIBUTIONS…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Process evaluation of codesign indicates that reflexive practice, coleadership models and reciprocal learning are valued strategies to support the inclusion of theory into a user-driven approach to healthcare codesign. 30 Strategies that require discussion, action and reflection beyond codesign meetings necessitate additional time and resource, which must be recognised and supported by leaders and researchers as an important part of preparing for and undertaking this study. 6,20 AUTHOR CONTRIBUTIONS…”
Section: Discussionmentioning
confidence: 99%
“…A reflexive approach that focuses on relationship building and reciprocal learning between codesign members and with researchers provides the basis for enabling facilitators and codesign groups to reflect on points at which the group have made critical design decisions or deviated from the initial ideas of members. 30 Observing video-recordings of codesign meetings may aid facilitators and members to consider and spot power imbalances, or moments where power shifted. 31 The use of theory in codesign and associated risks raise wider questions of the role of academic or clinician researchers who are tasked with facilitating a codesign process-what is the scope of their role, can academic/clinical subject matter experts facilitate, and what are the techniques that co-designers can employ to mitigate these risks?…”
Section: Pitfalls When Integrating Theory and Ways Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…Nic Giolla Easpaig and colleagues 4 present an evaluation of co-produced activities to enhance the safety of cancer care for culturally and linguistically diverse groups, which emphasises the importance of supporting and training lay people to participate fully in the coproduction of research. Page 5 argues that co-produced research needs to be guided by a clear and identified ethical framework, to guide its design and conduct.…”
Section: Co-production: Aspirations Definitions and Practicementioning
confidence: 99%